The Impact of Sambiloto Extract (Andrographis paniculata) as a Potential Antidiabetic Treatment - Clara Alverina; Nita Parisa; Rio Dwi Arliansyah; Nia Savitri Tamzil (Biomedical Journal of Indonesia, 2024)
Diabetes mellitus (DM) is a metabolic disease caused by an inappropriate increase in blood glucose levels. The development of traditional medicines, including extracts, fractions, and isolates from plants, remains highly intriguing and challenging. Andrographis paniculata is a one of medicinal plants with a long history of use in Asia for the treatment of various ailments. Andrographolide, a bioactive compound found in A. paniculata, has been extensively studied for its medicinal benefits, specifically its antidiabetic effects. This study employs a literature review approach to investigate the effect of Sambiloto extract (Andrographis paniculata) as an antidiabetic medication using Google Scholar, Science Direct, and PubMed databases. The publication year range for the literature data sources is from 2020 to 2024. Based on the conducted searches, three reference journals are included in this study. Andrographolide, the active compound contained in Sambiloto, may act as an antidiabetic medication through various mechanisms, thus representing a potential treatment for diabetes mellitus.